2013
DOI: 10.1111/ijac.12093
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Magnesium‐Doped Hydroxyapatite Prepared by Sol‐Gel Process

Abstract: Pure and doped hydroxyapatite (HA) nanocrystalline powders (Ca10‐xMgx(PO4)6OH2) were synthesized using sol‐gel process. For this, calcium nitrate tetrahydrate, magnesium nitrate hexahydrate, and phosphorous pentoxide were used as precursors for Ca, Mg, and P, respectively. Calculated amounts of magnesium ions (Mg+2) especially from 0 to 10% (molar ratio) were incorporated as dopant into the calcium sol solution. The structure and morphology of the gels obtained after mixing the phosphorous and (calcium + magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 53 publications
(99 reference statements)
0
24
0
Order By: Relevance
“…1) [30]. XRD pattern also showed the broadening of reflections due to the reduction in the crystallite size and increase in the lattice disorder, which were attributed to the Mg 2 þ substitution in the HA lattice (Table 2) [31]. In addition to the standard peaks for HA, two very low intensity peaks were also observed in the XRD pattern of Mg-SiHA and 1Ni-Mg-SiHA at 42.911 and 62.201, which were respectively assigned to the (2 0 0) and (2 2 0) reflection of magnesium oxide (MgO) (JCDPS no.…”
Section: Resultsmentioning
confidence: 94%
“…1) [30]. XRD pattern also showed the broadening of reflections due to the reduction in the crystallite size and increase in the lattice disorder, which were attributed to the Mg 2 þ substitution in the HA lattice (Table 2) [31]. In addition to the standard peaks for HA, two very low intensity peaks were also observed in the XRD pattern of Mg-SiHA and 1Ni-Mg-SiHA at 42.911 and 62.201, which were respectively assigned to the (2 0 0) and (2 2 0) reflection of magnesium oxide (MgO) (JCDPS no.…”
Section: Resultsmentioning
confidence: 94%
“…Walsh et al [10] synthesized mineralised red algae and reported XRD results that showed the conversion to hydroxyapatite (HA) at 100 °C for 14 h was successful and the composition of the obtained HA was characterized to be 64% HA, 33% CaCO 3 and 3% TCP, reinforcing that a 100% conversion under these conditions was not achievable. The longer processing time in this study (28 h) may be due to the presence of magnesium, which has an inhibitory effect on the HA crystal growth and increases the lattice disorder [19] . However, maintaining the conversion process at high pH (pH > 10) and longer processing time improves the formation of the HA layer on the shell surface [20] , which appears to be the case in the present study.…”
Section: Thermogravimetric Analysismentioning
confidence: 95%
“…Recent studies have shown that HA can be produced by PEO of titanium and its alloys. Usually, however, long process times (>20 min) or two-step procedures are required and the HA produced is of low crystallinity 48,49 . In titanium oxidation using PEO other structures such as anatase, rutile, and phosphates are also produced.…”
Section: Introductionmentioning
confidence: 99%